CORRELATION BETWEEN PROBLEM FACED IN GRAMMAR AND WRITING ABILITY OF EFL UNIVERSITY STUDENTS - Nurma Dhona Handayani; Muhammad Johan (JEE (Journal of English Education), 2018)
Writing is the most difficult and complicated language skill which is learnt by almost the students in every level of education. Moreover, writing English is an inseparable part of students throughout their academic life. They commit different kinds of errors and mistakes in learning English as a foreign language which are due to poor knowledge with grammar, thus itoften appears to be a difficult task for them to write. These problems are very obvious in writing composition or any other essay. Some mistakes are normally made by students when they do not understand well about the English grammar. Commonly, many of the students make grammar mistakes in their English language learning especially in productive skill such as writing. Problems in foreign language learning especially in English areunavoidable. They are difficult enough to be avoided. Therefore, this research analyzed students’ problems in grammar that could be seen from their writing to see the correlation of grammar toward writing ability. It was important to do because the analysis could give some advantages for both students and lecturers as language teaching achievement. As the result, most of EFL University students had problem in grammar. They made error inusing kind of tenses. The problem could be seen from their writing which used wrong verb in the sentences. And, it made their writing incorrect. Moreover, it proved that there was a significance correlation between problem faced in grammar and writing ability of EFL university students.